Sequestsome-1/p62-targeted small molecules for pancreatic cancer therapy. Issue 1 (January 2022) - Cuyler, Jacob; Murthy, Pranav; Spada, Neal G.; McGuire, Terence F.; Lotze, Michael T.; Xie, Xiang-Qun
Highlights: Pancreatic cancer autophagy promotes immune evasion and chemotherapeutic resistance. SQSTM1 is central to autophagy and associated immunosuppressive signaling pathways. Inhibitors of SQSTM1′s multifocal signaling domains warrant drug development. Abstract: Pancreatic ductal adenocarcinoma (PDAC) is characterized by heightened autophagy and systemic immune dysfunction. Modest improvements in clinical outcomes have been demonstrated in completed clinical trials targeting autophagy with combination hydroxychloroquine (HCQ) and chemotherapy. Recent mechanistic insights into the role of autophagy-dependent immune evasion have prompted the need for more precise and druggable targets of autophagy inhibition. Sequestosome-1 (SQSTM-1) is a multidomain scaffold protein with well-established roles in autophagy, tumor necrosis factor alpha (TNF α )- and NF- κ B-related signaling pathways. SQSTM1 overexpression is frequently observed in PDAC, correlating with clinical stage and outcome. Given the unique molecular structure of SQSTM-1 and its diverse activity, identifying means of limiting SQSTM-1-dependent autophagy to promote an effective immune response in PDAC could be a promising treatment strategy.